Regulation of pattern recognition receptor signaling by palmitoylation - Xiaocui Li; Xiaofang Hu; Hongjuan You; Kuiyang Zheng; Renxian Tang; Fanyun Kong (iScience)
Summary: Pattern recognition receptors (PRRs), consisting of Toll-like receptors, RIG-I-like receptors, cytosolic DNA sensors, and NOD-like receptors, sense exogenous pathogenic molecules and endogenous damage signals to maintain physiological homeostasis. Upon activation, PRRs stimulate the sensitization of nuclear factor κB, mitogen-activated protein kinase, TANK-binding kinase 1-interferon (IFN) regulatory factor, and inflammasome signaling pathways to produce inflammatory factors and IFNs to activate Janus kinase/signal transducer and activator of transcription signaling pathways, resulting in anti-infection, antitumor, and other specific immune responses. Palmitoylation is a crucial type of post-translational modification that reversibly alters the localization, stability, and biological activity of target molecules. Here, we discuss the available knowledge on the biological roles and underlying mechanisms linked to protein palmitoylation in modulating PRRs and their downstream signaling pathways under physiological and pathological conditions. Moreover, recent advances in the use of palmitoylation as an attractive therapeutic target for disorders caused by the dysregulation of PRRs were summarized.